Three-dimensional reconstruction-guided modified arterial-based complexity scoring system for nephron-sparing surgery: comparative outcomes of on-clamp and off-clamp tumor enucleation in renal cell carcinoma - Xu, Congcong; Jiang, Yiwei; Du, Jiaqi; Yang, Kefan; Zhong, Qifeng; Liu, Dekai; Zhang, Cheng; Zheng, Yichun (Frontiers in Surgery, 2025)
BackgroundVarious modalities of nephron-sparing surgery (NSS) exist; however, a comprehensive standard for determining the most suitable approach for specific kidney cancer patients remains elusive. This study aims to establish a novel scoring system that will assist urologists in formulating tailored surgical plans.MethodsWe conducted a comparative assessment of perioperative and prognostic data for these surgical types, alongside tumor contact surface area and arterial-based complexity of 205 patients for classification and regression analysis. Finally, a modified arterial-based complexity (mABC) scoring system was developed to enhance this assessment methodology.ResultsDespite no statistical differences in demographic data, we found that the off-clamp tumor enucleation (TE) group experienced greater estimated blood loss, drainage, catheterization, and longer hospital stays compared to the other two groups. However, this group also had shorter surgical times and less kidney function impairment, particularly in patients with renal dysfunction. Subgroup analysis indicated that when the mABC score was ≥4, patients in the off-clamp TE group showed significant increases in the rate of reduction in eGFR, blood loss, postoperative complications, postoperative drainage volume, and postoperative hospital days compared to patients in the other two groups.ConclusionsThe findings indicate that patients with fewer challenges in renal surgery may benefit from off-clamp TE, while those facing greater difficulty may find on-clamp TE more appropriate. This distinction, based on mABC scoring criteria, emphasizes the importance of tailoring the surgical approach to individual patient needs.Trial RegistrationOur study has been approved by the Ethics Committee of The Fourth Affiliated Hospital of Zhejiang University School of Medicine (K2023003) on 10/02/2023 and by clinical trials (NCT05790122) on 27/03/2023.